Analisis Pengaruh Belanja Modal Infrastruktur dan Belanja Modal Kesehatan Terhadap Pertumbuhan Ekonomi Inklusif di Kabupaten/Kota Provinsi Sulawesi Tenggara - Ahmad; Muh. Armawaddin; Harlifa (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effect of infrastructure capital expenditure and health capital expenditure on inclusive economic growth (Poverty and Unemployment) in 17 Regencies/Cities in Southeast Sulawesi Province. This study is a quantitative study using secondary data sourced from the Central Statistics Agency of Southeast Sulawesi Province and the Directorate General of Fiscal Balance of the Republic of Indonesia. The analysis method used is panel data regression analysis with the Fixed Effect Model (FEM) model using the Eviews 12 analysis tool. The results of the study show that infrastructure capital expenditure and health capital expenditure have a negative and insignificant effect on poverty. In addition, infrastructure capital expenditure has a negative and insignificant effect on unemployment and health capital expenditure has a positive and significant effect on unemployment.